2019
DOI: 10.1083/jcb.201807165
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic scaling of active zone scaffolds maintains global synaptic strength

Abstract: The mechanisms that stabilize synaptic strength are enigmatic. Goel et al. demonstrate that the abundance and nanostructure of scaffolds at presynaptic active zones are bidirectionally scaled to homeostatically calibrate global neurotransmitter release at the Drosophila melanogaster neuromuscular junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 98 publications
(262 reference statements)
11
96
0
Order By: Relevance
“…3G). These results parallel recent studies that have shown that while the number and intensity of individual active zones can vary at NMJs, the total abundance of active zone protein remains constant (Goel et al, 2019a; Goel et al, 2019b; Graf et al, 2009). Together, hyper-innervated NMJs express a target-specific reduction in both the number and intensity of release sites and a parallel reduction in presynaptic release probability that stabilizes synaptic strength, while no reciprocal changes are observed at hypo-innervated counterparts.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…3G). These results parallel recent studies that have shown that while the number and intensity of individual active zones can vary at NMJs, the total abundance of active zone protein remains constant (Goel et al, 2019a; Goel et al, 2019b; Graf et al, 2009). Together, hyper-innervated NMJs express a target-specific reduction in both the number and intensity of release sites and a parallel reduction in presynaptic release probability that stabilizes synaptic strength, while no reciprocal changes are observed at hypo-innervated counterparts.…”
Section: Resultssupporting
confidence: 89%
“…We considered four additional possible mechanisms that could, in principle, contribute to the observed enhancement in quantal size at hypo-innervated NMJs. First, increased presynaptic vesicle size could lead to enhanced glutamate emitted per vesicle, as has been documented in endocytosis mutants and following overexpression of the vesicular glutamate transporter (Daniels et al, 2004; Goel et al, 2019a). Second, multivesicular release has been observed in some systems (Rudolph et al, 2015) and was raised as a possibility in the original study to potentially explain the increased quantal size (Davis and Goodman, 1998), although there remains no evidence for multi-vesicular release at the fly NMJ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of Syt-GFP puncta in a single brain yielded a value for average puncta number, surface area, and volume ( Figure 3B). In support of this assay, we confirmed that an increase in synaptic contacts can be visualized as a greater number of Syt-GFP puncta: we examined Syt-GFP expression in PI-STAT neurons in which EndophilinA, an endocytic gene previously shown to cause synaptic 25 overgrowth, had been knocked down (STAT-Gal4>UAS-endoA-RNAi), and observed a corresponding increase in Syt-GFP puncta ( Figure S2) (Goel et al, 2019).…”
Section: Establishment Of Presynaptic Bouton Number As a Measurement supporting
confidence: 65%